Assessment of Management Scenarios to Reduce Loggerhead Turtle Interactions with Shrimp Trawlers in Georgia. Issue 1 (13th November 2013) - Scott, Jason A.; Dodd, Mark G.; Castleberry, Steven B.
Abstract: Recovery of loggerhead turtle Caretta caretta populations depends on many factors, including reducing anthropogenic mortality of adult turtles. Shrimp trawls are considered a major source of mortality for adult loggerhead turtles despite the mandatory use of turtle excluder devices. We modeled scenarios for reducing the likelihood of interaction between nesting adult loggerhead turtles and shrimp trawlers operating off the coast of Georgia during the nesting season (May–August). We used satellite telemetry and aerial surveys to describe the distribution patterns of nesting adult female turtles (2004–2005; n = 22) and shrimp trawls (1999–2005), respectively, across waters adjacent to the Georgia shoreline. Adult female turtles and shrimp trawlers both occupied state waters extensively during the nesting season. Turtles tended to have long, narrow home ranges that were located parallel to shore and that overlapped with the shrimp trawl distribution, which showed a slight grouping around deep channels. We modeled the efficacy of fleet reductions and spatial closures (accounting for fleet redistribution) in reducing shrimp trawler activity around loggerhead turtles. A comparison of spatial closures indicated that a large closure of state waters (∼200 km 2 ) east of Sapelo and Blackbeard islands would reduce mean trawler activity levels in turtle home ranges. We also found that fleet reductions of 50% or more reduced potential interactions between turtles and trawlers. Although spatial closures produced a net total reduction in turtle–trawler interactions, fleet reductions yielded a reduction in such interactions across the study area. We recommend that to reduce loggerhead turtle–trawler interactions, state agencies should consider a limited‐entry system or some other means to limit the number of vessels operating within state waters. Received October 2, 2012; accepted July 17, 2013